PRACTICALITY OF DEVELOPING INTERACTIVE MULTIMEDIA BASED ON MACROMEDIA FLASH 8 ON LEARNING INTEGRATED THEMATIC ELEMENTARY SCHOOL - Arespi Junindra Arespi Junindra; Yalvema Miaz; Yeni Karneli; Elfia Sukma (Universitas Majalengka, 2023)
The implementation of learning objectives cannot be separated from certain aspects, one of which is the aspect of learning media, including interactive multimedia, which is very suitable for learning in the current technological era. However, the implementation in the field related to the use of interactive multimedia in learning has not been optimal, including the lack of optimal use of interactive multimedia based on computer applications, even though the facilities and infrastructure are adequate. This research aims to develop interactive multimedia based on Macromedia Flash 8 for integrated thematic learning in practical elementary schools. This type of research is R&D using the 4-D model consisting of four stages: define, design, develop, and disseminate. The subjects of this study were the fifth-grade students at SDN 32 Bungo Pasang, SDN 45 Bungo Pasang, and SDN 51 Bungo Pasang, Koto Tangah District, Padang City, totaling 62 students. The research data collection instrument was through practicality sheets, namely the educator's response questionnaire and the student's response questionnaire. The results showed that the practicality level of interactive multimedia was obtained with the teacher's response value of 95.56% in the